2021
DOI: 10.3390/su13041652
|View full text |Cite
|
Sign up to set email alerts
|

Temporary Use as a Participatory Placemaking Tool to Support Cultural Initiatives and Its Connection to City Marketing Strategies—The Case of Athens

Abstract: For many cities, abandoned or underused spaces pose a major challenge, but temporary use is being manifested as a tool that can offer solutions. So-called “meanwhile spaces” provide opportunities for city officials to create the conditions for the cultural economy to be supported while simultaneously meeting urban regeneration goals and supporting city marketing purposes. In European cities, such as Berlin, Ghent, Nantes, and Bremen, there are examples where “temporary urbanism” is being incorporated into main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…From the point of view of the city authorities, the provision and reorganization of public spaces is such an important initiative that it is used as one of the main elements of city marketing campaigns which create the city's identity. A review article dealing with this issue showed that it had become part of image campaigns in places offering residents temporary use during pandemic (Karachalis, 2021). Cities more and more often use social initiatives and various types of integrating events to improve their image and reputation, departing from commercial, traditional forms of advertising (Govers, 2018).…”
Section: Perspective Of Residentsmentioning
confidence: 99%
“…From the point of view of the city authorities, the provision and reorganization of public spaces is such an important initiative that it is used as one of the main elements of city marketing campaigns which create the city's identity. A review article dealing with this issue showed that it had become part of image campaigns in places offering residents temporary use during pandemic (Karachalis, 2021). Cities more and more often use social initiatives and various types of integrating events to improve their image and reputation, departing from commercial, traditional forms of advertising (Govers, 2018).…”
Section: Perspective Of Residentsmentioning
confidence: 99%
“…To understand the depth and breadth of these responses, compiling a comprehensive list of crisis marketing initiatives undertaken by FMCG brands in Nigeria is imperative. Karachalis (2021) emphasized the importance of participatory placemaking tools in supporting cultural initiatives, especially in the context of city marketing strategies. Drawing parallels, FMCG brands in Nigeria leveraged community engagement and participatory marketing strategies to stay connected with their consumer base.…”
Section: Compilation Of Crisis Marketing Initiatives By Nigerian Fmcg...mentioning
confidence: 99%
“…Making the transition from the temporary to the permanent for the inhabitants is in this context a crucial aspect as a return to their original habitat is often not (immediately) possible for people who have moved to temporary shelter [3]. Other relevant applications address the experimentation with cultural activities [4] or the use of temporary vacant urban plots for the application of processes in a cultural context [5]. These creative applications of urban space or temporarily unused buildings have been extensively covered in one of the research papers that resulted from the here discussed project [6].…”
Section: Introductionmentioning
confidence: 99%